2020
DOI: 10.3390/ijgi9020129
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Effects of Spatially Structured Scoring Systems in Location-Based Serious Games—A Case Study in the Context of OpenStreetMap

Abstract: Location-based games have become popular in recent years, with Pokémon Go and Ingress being two very prominent examples. Some location-based games, known as Serious Games, go beyond entertainment and serve additional purposes such as data collection. Such games are also found in the OpenStreetMap context and playfully enrich the project’s geodatabase. Examples include Kort and StreetComplete. This article examines the role of spatially structured scoring systems as a motivational element. It is analysed how sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
(61 reference statements)
0
7
0
5
Order By: Relevance
“…This introduces the possibility of using gamification to assist with OSM quality management. Westerholt, Lorei, and Höfle (2020) examine the role of gamification in OSM by introducing and comparing spatially clustered and random scoring systems as a component for mapping motivation using the mobile game StreetComplete . Similar to this study, they studied the behaviour of participants, but they also found that user behaviour was altered by changing the game’s scoring system with respect to space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This introduces the possibility of using gamification to assist with OSM quality management. Westerholt, Lorei, and Höfle (2020) examine the role of gamification in OSM by introducing and comparing spatially clustered and random scoring systems as a component for mapping motivation using the mobile game StreetComplete . Similar to this study, they studied the behaviour of participants, but they also found that user behaviour was altered by changing the game’s scoring system with respect to space.…”
Section: Discussionmentioning
confidence: 99%
“…This introduces the possibility of using gamification to assist with OSM quality management. Westerholt, Lorei, and Höfle (2020) examine the role of gamification in OSM by introducing and comparing spatially clustered and random scoring systems as a component for mapping motivation using the mobile game StreetComplete.…”
Section: F I G U R Ementioning
confidence: 99%
“…The physical, social, and spatial aspects of locationbased games make them well suited to address real-world scenarios and conditions. With location-based games often requiring teamwork and collaboration, serious location-based games can entwine the social and cultural aspects of the areas in which they are played (Westerholt et al, 2020). However, there are key differences between serious games and location-based games and how each can transmit knowledge.…”
Section: Serious Gamesmentioning
confidence: 99%
“…While these games have entertainment as the primary goal, they are also well suited for achieving secondary goals, such as learning (Laine, 2018;Ribeiro et al, 2021) and physical activity (Althoff et al, 2016;Ellis et al, 2020;Laato et al, 2020). They can thereby also be considered Serious Location-based Games (SLGs)-understood as location-based games serving additional purposes beyond entertainment (Westerholt et al, 2020), such as learning and physical activity-as name above-or data collection and fostering teamwork or collaboration contextualized in social and cultural aspects of the game tasks. From a didactical perspective, learning-focused SLGs feature tools and characteristics that make their use as learning tools very appealing: SLGs guide learners to a real object's location and supplement these objects explicitly or implicitly with educational information (Walker et al, 2017).…”
Section: Editorial On the Research Topic "Serious Location-based Games"mentioning
confidence: 99%